BIOLOGICAL EFFICIENCY OF DUPLET TT 22.5% EM.C. PREPARATION AGAINST THE MAIN DISEASES OF JUNIPER (Texas Journal of Medical Science, 2024)
In the article, Duplet TT 22.5% em.k drug was used in juniper against phomopsis, rust, diplodiosis, microterium diseases at a consumption rate of 0.5 l/ha. The biological efficiency of the drug against diseases was phomopsis 82.2%, rust 85.7%, diplodiosis 84.9%, microtherium 85.1%, and other data were given.